Economic cybernetics of energy saving measures in the electrical networks of electricity consumers - Omelchuk, A.; Zakolodyazhnyi, V.; Timokhina, A.; Lozova, M. (Energy and Automation, 2024)
Effective practical actions for energy saving are work on the normalization of reactive power flows and its compensation. This will be the beginning of a global process of reducing electricity losses in electrical networks, which is equivalent to the construction of additional generating capacities, but with lower costs. The article simulates the mode of operation of a regulated capacitor unit (CU) with a voltage of 0.4 kV in order to assess the economic efficiency of its operation in electrical networks of industrial electricity consumers. The mode of active and reactive load of the electric network was analyzed, the choice of the optimal power of the regulated CU was substantiated, and indicators of the economic efficiency of reactive power compensation were investigated on the considered example of the electric network. According to current regulatory documents, reactive flows of a certain amount from the networks of supply organizations to the network of consumers require their payment or the use of means of compensation for these flows. In addition, reactive flows limit the bandwidth of electrical power networks. In order to increase the efficiency of electricity consumption and the throughput of electrical power networks, an algorithm for selecting the parameters of the CU and evaluating the economic efficiency of its operation is proposed. Key words: power losses, reactive power compensation, voltage deviation, capacitor banks, bandwidth